2017
DOI: 10.4018/ijwsr.2017040103
|View full text |Cite
|
Sign up to set email alerts
|

A Location-Context Awareness Mobile Services Collaborative Recommendation Algorithm Based on User Behavior Prediction

Abstract: Nowadays, location based services (LBS) has become one of the most popular applications with the rapid development of mobile Internet technology. More and more research is focused on discovering the required services among massive information according to the personalized behavior. In this paper, a collaborative filtering (CF) recommendation algorithm is presented based on the Location-aware Hidden Markov Model (LHMM). This approach includes three main stages. First, it clusters users by making a pattern simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Other studies reported satisfactory results with their presented solutions and pointed in the direction of validating those approaches with other real-world data sets [24], [172], and exploring deeply other attributes associated with geotagged events [23], [62]. Furthermore, other authors plan to optimize the training of their models, and/or explore other ad-vanced techniques such as deep learning [67], [140].…”
Section: B Research Opportunitiesmentioning
confidence: 88%
See 3 more Smart Citations
“…Other studies reported satisfactory results with their presented solutions and pointed in the direction of validating those approaches with other real-world data sets [24], [172], and exploring deeply other attributes associated with geotagged events [23], [62]. Furthermore, other authors plan to optimize the training of their models, and/or explore other ad-vanced techniques such as deep learning [67], [140].…”
Section: B Research Opportunitiesmentioning
confidence: 88%
“…• Behavioral pattern detection: Location context is exploited to detect or infer behavioral patterns among elements of a system. One common use case is exploiting the movement behavior of users to improve mobile services [23]. • Predictive analysis: This problem type is analogous to predictive analytics or supervised learning.…”
Section: Location Context Problem Typesmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the strong correlation between time and geographical location, the study introduced time characteristics into location recommendations and used it to improve the performance of location recommendation [32,33]. In terms of research data, the data sources used in the current location recommendation can be divided into two categories: (1) user information, which includes the profile, location history and t track of users [34][35][36][37]; and (2) characteristics of the location, such as the number of users visiting a certain place and physical properties such as malls and parks [38][39][40]. Although researchers have proposed numerous new methods and models, they have continued to promote the development of location recommendation research.…”
Section: Introductionmentioning
confidence: 99%